Organizational stressor of staff negative behaviors among higher education deans: a post positivist multiple case study - Chan, Alfred Huan Zhi; Mohd Dahlan Hj Malek; Ferlis Bahari (2016)
Organizations and institutions today are now seeing rise of organizational stress and how it is directly contributing to the rise of financial and personal cost of mental health issues among its workers (Patty, 2016). The all important field of higher education is not spared and is also undergoing a paradigm shift, as a historically low competition industry to a sudden highly competitive industry (Otara, 2015). With these drastic changes, higher education deans are now plagued by a myriad of organizational stressors. A qualitative case study approach was used to investigated this phenomenon, encompassing the interview techniques of Patton (2002) and the validity and reliability exercises of Creswell (2014). Deans from one institution was found to encounter staff related organizational stressors which consisted of lecturer low performance, lecturer going against dean, lecturer against lecturer, lecturer negative behavior, lecturer low work ethic, and administrative staff negative work elements. This confirmed on the existence of organizational stressors among higher education deans and may be used to spur future research to reduce or eliminated this phenomenon.